The legacy of state socialism on attitudes toward immigration - Martin Lange (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
Does the politico-economic system affect preferences for immigration? In this study, I show that individuals exposed to life under state socialism have formed and persistently hold different attitudes toward immigration. By exploiting the division and reunification of Germany, I estimate the influence of state socialism on attitudes toward immigration. Drawing on rich individual panel data, I find that East Germans who lived under state socialism, are 15 percent more likely to oppose immigration than West Germans who spent their entire life in a democratic, capitalist country. This difference in attitudes toward immigration is persistent over time and across space, and largest for cohorts born and raised under state socialism. This gap in attitudes can be traced back to a longer-term deterioration in trust. Evidence from members of a group that opposed the authoritarian system highlights the importance of state socialist ideology for attitude formation.
Keywords: P20; P51; N34; Z10; 330; state socialism; attitudes toward immigration; German division andreunification